Genetic, morphological and acoustic differentiation of African trident bats (Rhinonycteridae: Triaenops). Issue 1 (17th September 2020) - Rossoni, Daniela M; Demos, Terrence C; Goodman, Steven M; Yego, Richard K; Mohlman, Jessica L; Webala, Paul W; Patterson, Bruce D
Abstract: Rhinonycteridae (trident bats) are a small Palaeotropical family of insectivorous bats allied to Hipposideridae. Their taxonomy has been in a state of flux. Here, we use mitochondrial and nuclear sequences to evaluate species relationships, confirming the monophyly of both Triaenops and Paratriaenops . Although most Triaenops afer specimens are recovered as a group, mitochondrial analyses strongly support some Kenyan individuals as members of Triaenops persicus . Analyses of four nuclear introns (ACOX2, COPS7A, RODGI and STAT5A) strongly support the mitochondrial topology. Morphometric analysis of the skull, external morphology and echolocation calls confirm that the Triaenops from the Rift Valley in Kenya (Nakuru, Baringo and Pokot counties) are distinct from typical T. afer in coastal (Kilifi and Kwale counties) or interior (Laikipia and Makueni counties) colonies. We interpret these analyses to indicate that two species of Triaenops occur in East Africa: T. afer in coastal regions along the Indian Ocean and in the highlands of central Kenya and Ethiopia, and T. persicus in the Rift Valley of Kenya. Although they appear widely disjunct from Middle Eastern populations, Kenyan T. persicus might be more widely distributed in the Rift Valley; they are somewhat differentiated from Middle Eastern populations in terms of both cranial morphology and vocalizations.